2016
DOI: 10.17576/gema-2016-1603-07
|View full text |Cite
|
Sign up to set email alerts
|

Written Corrective Feedback: Preferences and Justifications of Teachers and Students in a Thai Context

Abstract: This study investigates the preferences and justifications of teachers and students on written corrective feedback (WCF) at a tertiary institution in Thailand and is aimed at expanding on prior similar studies conducted with smaller data sets in different contexts. Quantitative and qualitative questionnaire data were collected from 262 intermediate students and 21 teachers in order to test two hypotheses: (1) teachers' and students' WCF preferences would differ significantly, and (2) their justifications for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 20 publications
5
28
0
1
Order By: Relevance
“…Cohen & Cavalcanti, 1990;Lee, 2008), or because of the possible discrepancy between what kind of feedback teachers provide and what students would like to get (e.g. Black & Nanni, 2016;Cohen & Cavalcanti, 1990)? There also appears to be a gap between what feedback teachers report giving and what students report getting (Cohen & Cavalcanti, 1990).…”
Section: Studies On Feedback In Foreign or Second Language Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen & Cavalcanti, 1990;Lee, 2008), or because of the possible discrepancy between what kind of feedback teachers provide and what students would like to get (e.g. Black & Nanni, 2016;Cohen & Cavalcanti, 1990)? There also appears to be a gap between what feedback teachers report giving and what students report getting (Cohen & Cavalcanti, 1990).…”
Section: Studies On Feedback In Foreign or Second Language Educationmentioning
confidence: 99%
“…Quite recently, however, there have been some such studies. For instance, the studies by Amrhein and Nassaji (2010) as well as Black and Nanni (2016) compared teachers' and students' perceptions and preferences over different methods of written CF. The results of both these studies indicated that students' and teachers' preferences as well as their justifications differed somewhat (Amrhein & Nassaji, 2010;Black & Nanni, 2016).…”
Section: Studies On Feedback In Foreign or Second Language Educationmentioning
confidence: 99%
“…Furthermore, students' preferences for certain types and amounts of WCF were reported to partly account for the effectiveness of WCF because their preferences affect their use of it for learning (Ferris, 1995;Lee, 2005). For the effectiveness of WCF, the incongruity between students' and teachers' perceptions regarding WCF should therefore be avoided (Black & Nanni, 2016). Moreover, Ellis (2009), Guénette (2007) and Hyland and Hyland (2006) also emphasized that there is no best way to do WCF because its success or failure depends on the classroom setting, students' previous learning experiences, types of errors, writing tasks and a collection of other unknown variables.…”
Section: Introductionmentioning
confidence: 99%
“…With the multifaceted nature of WCF and in the reported culturally-based English learning and teaching context in Thailand (Black & Nanni, 2016;Root, 2016), how teachers practice this teaching technique with their students has not been documented in the literature. This study is expected to shed more light on how WCF is applied and its effectiveness in Thailand where English has been taught as a foreign language and a separate subject for decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation